2019
DOI: 10.1167/iovs.18-24869
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tissue-Engineered Corneal Stromal Equivalent Based on Amniotic Membrane and Keratocytes

Abstract: PURPOSE. To investigate a novel strategy in constructing tissue-engineered corneal stromal equivalent based on amniotic membrane and keratocytes. METHODS. The ultrathin amniotic membrane (UAM) was laminated, with corneal stromal cells (CSCs) distributed between the space of the layered UAMs. Calcein AM staining was used to evaluate cellular viability, morphology, and arrangement. Immunostaining, qRT-PCR, and Western blot were performed to detect gene and protein expression in keratocytes. Optical coherence tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The correlation among seven samples was tested by the Spearman's rank correlation coefficient test, and the resulting correlation matrix was drawn with the 'ggcorrplot' library of R. In the heatmap analysis, the values were normalized with 'zFPKM' and heatmap analysis was performed with 'pheatmap' (both the libraries were obtained from Bioconductor). Marker genes reported to show specific expression in different corneal tissues, such as the epithelium, stroma, and endothelium, were selected as follows: PAX6 and WNT7 were referred from a representative study that performed a functional analysis of the corneal epithelium 31 ; ALDH3A1, CHST6, KERA, and PTGDS were extracted from expression markers of the corneal stroma or keratocytes commonly reported in four articles [32][33][34][35] ; and ATP1A1, TJP1, COL8A1, and SLC4A11 were selected from highly ranked investigated genes related to the corneal endothelium in a comprehensive review article 36 . The expression data of each gene used in the heatmap were evaluated for the existence of outlier samples by the Smirnov-Grubbs test with the 'outliers' library of R.…”
Section: Rna-seq Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation among seven samples was tested by the Spearman's rank correlation coefficient test, and the resulting correlation matrix was drawn with the 'ggcorrplot' library of R. In the heatmap analysis, the values were normalized with 'zFPKM' and heatmap analysis was performed with 'pheatmap' (both the libraries were obtained from Bioconductor). Marker genes reported to show specific expression in different corneal tissues, such as the epithelium, stroma, and endothelium, were selected as follows: PAX6 and WNT7 were referred from a representative study that performed a functional analysis of the corneal epithelium 31 ; ALDH3A1, CHST6, KERA, and PTGDS were extracted from expression markers of the corneal stroma or keratocytes commonly reported in four articles [32][33][34][35] ; and ATP1A1, TJP1, COL8A1, and SLC4A11 were selected from highly ranked investigated genes related to the corneal endothelium in a comprehensive review article 36 . The expression data of each gene used in the heatmap were evaluated for the existence of outlier samples by the Smirnov-Grubbs test with the 'outliers' library of R.…”
Section: Rna-seq Data Analysesmentioning
confidence: 99%
“…PAX6 and WNT7A, which are expressed in the corneal epithelium 31 , showed low expression in the endothelium. Most genes with known expression in the stroma [32][33][34][35] showed low expression levels in the endothelium, although the Prostaglandin D2 synthase (PTGDS) gene was highly expressed. However, this high expression of PTGDS is consistent with a report indicating that PTGDS is expressed in both the stroma and the endothelium 38 .…”
Section: Technical Validationmentioning
confidence: 99%
“…Stromal cell-based strategies require ex vivo propagation of CSKs. However, CSKs obtained from donor corneas are challenging to propagate under standard culture conditions [13,14]. Using serum and growth factor-supplemented media, CSKs rapidly differentiate into stromal fibroblasts (SFs) and lose specific keratocyte features, including the expression of keratan sulphate proteoglycans (lumican, keratocan), which regulates collagen fibril alignment and spacing, and stromal crystallins (transketolase, aldehyde dehydrogenase ALDH1A1 and 3A1) for transparency and refractivity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Human amnion is known to exert anti-inflammatory, anti-microbial and anti-scarring effects, secrete immunosuppressive factors and promote epithelial wound healing [19][20][21][22][23][24][25][26][27]. Amnion stroma has been shown to contain growth factors and bioactive substances in regulating TGFÎČ signalling that support CSK propagation [14,18,28,29]. It remains unknown whether amnion cryo-storage interferes with its ability to promote CSK growth in culture.…”
Section: Introductionmentioning
confidence: 99%
“…33 Che et al have recently described the fabrication of stromal equivalents by stacking cell-seeded ultrathin amniotic membrane. 34 In this case, an extended culture period of 8 weeks allowed the stromal cells to produce ECM to bind the layers. The constructs reported in our present study were fabricated with materials found in the native stroma, which might present advantages for clinical translation.…”
Section: Discussionmentioning
confidence: 99%